Review of the millipede genus Propyrgodesmus Silvestri, 1920, with the description of a new species from a sacred grove in Kerala, India (Diplopoda: Polydesmida: Pyrgodesmidae) - Aswathy, Mathilakath Dasan; Sudhikumar, Ambalaparambil Vasu (Zootaxa, 2022)
The endemic Indian genus Propyrgodesmus is reviewed, rediagnosed and shown to presently comprise three species, all illustrated, keyed and mapped, including P. bulbogonopus sp. nov., from a sacred grove supporting a semi-evergreen vegetation in Kerala, southern India. The new species differs from their congeners, P. lobulatus Silvestri, 1920 (the type species) and P. frater Carl, 1932, mainly by tergal ornamentations and, when known, some significant details of gonopodal structure.